2014
DOI: 10.4271/2014-01-2857
|View full text |Cite
|
Sign up to set email alerts
|

General Procedure for the Determination of Heat Transfer Properties in Small Automotive Turbochargers

Abstract: These days many research efforts on internal combustion engines are centred on optimising turbocharger matching and performance on the engine. In the last years a number of studies have pointed out the strong effect on turbocharger behaviour of heat transfer phenomena. The main difficulty for taking into account these phenomena comes from the little information provided by turbocharger manufacturers. In this background, Original Engine Manufacturers (OEM) need general engineering tools able to provide reasonab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…A hypothesis of mean temperature for oil is done according to the temperature values calculated previously in order to maintain the lubrication of turbocharger under safe conditions. The convective conductance between the oil and H2 metal node needs to be calculated through dimensionless numbers of Reynolds, Prandtl, Nusselt and additional external geometry using proposed correlations [27] . The convective heat transfer coefficient for the oil and water can be obtained with equation 3, where k is the conductivity of the fluid and D refers to the diameter of the inlet port.…”
Section: Modelling Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hypothesis of mean temperature for oil is done according to the temperature values calculated previously in order to maintain the lubrication of turbocharger under safe conditions. The convective conductance between the oil and H2 metal node needs to be calculated through dimensionless numbers of Reynolds, Prandtl, Nusselt and additional external geometry using proposed correlations [27] . The convective heat transfer coefficient for the oil and water can be obtained with equation 3, where k is the conductivity of the fluid and D refers to the diameter of the inlet port.…”
Section: Modelling Results and Discussionmentioning
confidence: 99%
“…Finally equation (4) represents the integral of the heat flow already calculated, which can be used to estimate the acting time for the auxiliary pump system. C is the sum of all capacitances of the five metal nodes of the turbocharger thermal, obtained experimentally [27,29], and ∆ is the temperature decrease from an initial case simulated that lack of any type of extra cooling after the hot-stop. ∫̇ = ⋅ ∆…”
Section: Modelling Results and Discussionmentioning
confidence: 99%
“…The actual mass flow through waste-gate and by-pass valves is calculated as the difference between the measured mass flow through both turbines and 64 3.3. Gas stand 6. This is possible due to the availability of manufacturers maps of both the HPT and the LPT.ṁ…”
Section: By-pass and Waste-gate Valves Flow Characterisationmentioning
confidence: 99%
“…The final appearance of an instrumented turbocharger with wall thermocouples is shown in Figure 3. 6. It can be observed that different axial sections have been chosen in which three thermocouples for each section have been installed.…”
Section: Heat Transfer Characterization Testsmentioning
confidence: 99%
See 1 more Smart Citation